1996
DOI: 10.3109/17453679608994683
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy after cruciate knee surgery Skin, subcutaneous and articular temperatures in 8 patients

Abstract: We recorded temperature changes on the skin surface, subcutaneously and intra-articularly during cryotherapy after knee surgery by using Cryo-cuff compression dressings. Subcutaneous recordings on the contralateral knee were used as reference. 8 patients were examined. There was a reproducible decrease in skin temperature and subcutaneous temperature. Skin temperature had to be lowered to about 20 degrees C to obtain demonstrable intraarticular temperature changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…The cooling effect was more prominent on the skin and in the joint capsule than intra-articularly. These findings are consistent with previous studies involving cryotherapy following joint surgery 16,17 . The knee arthroscopy procedure itself lowers the temperature of the knee joint, as it involves irrigation with room-temperature saline solution 18 .…”
Section: Discussionsupporting
confidence: 94%
“…The cooling effect was more prominent on the skin and in the joint capsule than intra-articularly. These findings are consistent with previous studies involving cryotherapy following joint surgery 16,17 . The knee arthroscopy procedure itself lowers the temperature of the knee joint, as it involves irrigation with room-temperature saline solution 18 .…”
Section: Discussionsupporting
confidence: 94%
“…Several in-vivo studies have demonstrated the efficacy of conventional ice therapy and commercial cryotherapy systems in reducing skin, intramuscular, and intra-articular temperature in healthy volunteers, 16 patients with inflammatory conditions, 17,18 and those after surgery, 19 including ACL reconstruction. 6,10,13,20 While the optimal duration and frequency of cryotherapy are often subject to debate, 21 many authors assert that lower temperatures contribute to decreased tissue metabolism, localized vasoconstriction, diminished inflammatory mediator release, hypoxia, and attenuated nerve conduction with a resultant decrease in secondary edema, pain, and spasm. 6,22 Several clinical studies have demonstrated improvement in objective and subjective outcome measures with cryotherapy after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Cryotherapy results in significant reductions in cellular metabolism, tissue hypoxia, edema formation, nerve conduction, and secondary pain. 6,7 Similarly, cold treatment has been successfully used in the postsurgical treatment of orthopedic patients, particularly following anterior cruciate ligament (ACL) reconstruction, [8][9][10][11][12][13] knee arthroscopy, 14 and total knee arthroplasty. 15 Although the actual therapeutic benefits have been disputed, 4,8,14 several authors have demonstrated the efficacy of continuous cold therapy in the short-term postoperative period.…”
mentioning
confidence: 99%
“…Meeusen and Lievens [9] and Matsen et al [12] found significantly more swelling in the limbs that were cooled below 15°C compared with controls, probably due to an increased permeability of lymph vessels and capillaries. After 6 h of cryocuff therapy, Dahlstedt et al [4] found a temperature reduction of skin about the knee to 20°-28°C and of subcutis to 27°-34°C. These temperatures should be well outside the danger levels.…”
Section: Discussionmentioning
confidence: 99%